A perceptual representation in the frontal eye field during covert visual search that is more reliable than the behavioral report - Trageser, Jason C. (2008)
Neuronal activity in the frontal eye field (FEF) identifies locations of behaviorally important objects for guiding attention and eye movements. We recorded neural activity in the FEF of monkeys trained to manually turn a lever towards the location of a pop-out target of a visual search array without shifting gaze. We examined whether the reliability of the neural representation of the salient target location predicted the monkeys’ accuracy of reporting target location. We found that FEF neurons reliably encoded the location of the target stimulus not only on correct trials but also on error trials. The representation of target location in FEF persisted until the manual behavioral report but did not increase in magnitude. This result suggests that, in the absence of an eye movement report, FEF encodes the perceptual information necessary to perform the task but does not accumulate this sensory evidence towards a perceptual decision threshold. These results provide physiological evidence that, under certain circumstances, accurate perceptual representations do not always lead to accurate behavioral reports and that variability in processes outside of perception must be considered to account for the variability in perceptual choice behavior.